PERSPEKTIF NILAI PESANTREN: PENGEMBANGAN KUALITAS PRIBADI IDEAL KONSELOR - Ishlakhatus Sa’idah; Moh. Ziyadul Haq Annajih (Ulumuna: Jurnal Studi Keilsman, 2019)
The personal quality of the counselor is very supportive of the process and results of counseling activities. However, in practice there are still often some problems related to the counselor's personal, although there have been many expert formulations about the personal qualities of the counselor. This is due to the standards used in the formulation of the personal qualities of the Western formula counselors that are not in accordance with the socio-psychological conditions of the Indonesian people. So it is important to attempt to internalize the values ​​of local wisdom into the formulation of the personal qualities of the counselor. One approach that can be used is a formula that is explored from the values ​​of pesantren. The aim of the study is to develop the personal qualities of counselors based on the values ​​of pesantren. This study uses a library study approach. The values ​​of boarding schools that can be extracted into the formulation of the ideal personal qualities of the counselor include, (1) sincerity, (2) patience, (3) firm and respectful, (4) caution, (5) openness, (6) pious, (7) compassion, and (8) fair.